Assessment of the phenotypic and physicochemical traits of nine Iranian endemic fenugreek (Trigonella foenum-graecum L.) - Majid Azizi; Hoda Saeb; Mansoureh Nazari; Hossein Aroiee; Mohammad Reza Morshedloo (Scientific Reports)
Abstract Considering the significance of fenugreek as a valuable medicinal and food plant, assessing the genetic diversity of different populations of this species is essential for optimizing performance and adaptability to environmental conditions. This study aims to investigate genetic diversity and identify important phenotypic traits in various Iranian fenugreek accessions (“Mashhad”, “Tehran”, “Yazd”, “Shiraz”, “Birjand”, “Isfahan”, “Kerman”, “Kalat”, “Neyshabur”), an experiment was conducted in a randomized complete block design with three replications and nine treatments (accessions) in Iran. The results showed that the highest seed yield was observed in “Kalat” (120.73 g/m2) and the lowest seed yield was observed in “Neyshabur” (29.28 g/m2) accessions. Also, “Isfahan” had the highest number of branches (10.8/plant), and the highest 1000-seed weight (29.6 g) was recorded in “Shiraz”. It was also found that the number of days to the appearance of the first flower and the arrival of the last pod was the least in the “Yazd” (50 and 85 days) and the highest in the “Kerman” (87.67 and 170 days), respectively. It was also found that the highest content of soluble sugar (0.32%) belonged to the “Mashhad” and the highest amount of total chlorophyll (2.36 mg/gfw) belonged to the “Isfahan” accessions. “Birjand” had the highest antioxidant activity (55.64%). The highest abundance of bluish spots was also seen in the “Kalat” accession. The results of this study showed a considerable diversity between the studied accessions. The most suitable accession for harvesting seeds was “Kalat” and the “Isfahan” accession was the most appropriate for harvesting herbal yield. The results of this study provide a valuable foundation for future research aimed at identifying specific genotypes with superior traits, such as higher yield or stress resistance. Future studies can build upon these findings by focusing on selecting and breeding elite fenugreek lines for use in crop improvement programs.